Technology-Facilitated Intimate Partner Abuse: a qualitative analysis of data from online domestic abuse forums. (4th May 2021) - Leitão, Roxanne
Abstract : This article reports on a qualitative analysis of data gathered from three online discussion forums for victims and survivors of domestic abuse. The analysis focussed on technology-facilitated abuse and the findings cover three main themes, namely, 1) forms of technology-facilitated abuse being discussed on the forums, 2) the ways in which forum members are using technology within the context of intimate partner abuse, and 3) the digital privacy and security advice being exchanged between victims/survivors on the forums. The article concludes with a discussion on the dual role of digital technologies within the context of intimate partner abuse, on the challenges and advantages of digital ubiquity, as well as on the issues surrounding digital evidence of abuse, and the labor of managing digital privacy and security.